Galanin Receptors as Drug Target for Novel Antidepressants: Review - Demsie DG (Dove Medical Press, 2020)
Desalegn Getnet Demsie,1 Birhanetensay Masresha Altaye,2 Etsay Weldekidan,1 Hagazi Gebremedhin,1 Niguse Meles Alema,3 Mulugeta Mihrete Tefera,3 Abere Tilahun Bantie4 1College of Medicine and Health Sciences, Department of Pharmacy, Adigrat University, Adigrat, Ethiopia; 2College of Health Sciences, Debre Berhan University, Debre Berhan, Ethiopia; 3Bahir Dar Health Science College, Bahir Dar, Ethiopia; 4College of Medicine and Health Sciences, Department of Anesthesia, Adigrat University, Adigrat, EthiopiaCorrespondence: Desalegn Getnet Demsie Tel +251 937404956Email desget361@gmail.comAbstract: Galanin (GAL) is a 29-amino-acid neuropeptide that serves multiple physiological functions throughout the central and peripheral nervous system. Its role involves in a range of physiological and pathological functions including control of food intake, neuro-protection, neuronal regeneration, energy expenditure, reproduction, water balance, mood, nociception and various neuroendocrine functions. The use of currently available antidepressant drugs raises concerns regarding efficacy and onset of action; therefore, the need for antidepressants with novel mechanisms is increasing. Presently, various studies revealed the link between GAL and depression. Attenuation of depressive symptoms is achieved through inhibition of GalR1 and GalR3 and activation of GalR2. However, lack of receptor selectivity of ligands has limited the complete elucidation of effects of different receptors in depression-like behavior. Studies have suggested that GAL enhances the action of selective serotonin reuptake inhibitors (SSRIs) and promotes availability of transcription proteins. This review addresses the role of GAL, GAL receptors (GALRs) ligands including selective peptides, and the mechanism of ligand receptor interaction in attenuating depressive symptoms.Keywords: Galanin (GAL), depression, Galanin (GAL) receptors